Facile fabrication of activated charcoal decorated functionalized multi-walled carbon nanotube electro-catalyst for high performance quasi-solid state dye-sensitized solar cells. (20th April 2017) - Memon, Anam Ali; Arbab, Alvira Ayoub; Sahito, Iftikhar Ali; Mengal, Naveed; Sun, Kyung Chul; Qadir, Muhammad Bilal; Choi, Yun Seon; Jeong, Sung Hoon
Graphical abstract: Highlights: Functionalized mesoporous carbon (f-MC) were synthesized for Pt free DSSC. f-MC CEs exhibit a very low charge transfer resistance of 0.6 Ω.cm 2 . f-MC CEs have superior electro-catalytic activity. DSSCs fabricated using f-MC counter electrode exhibit an efficiency of 8.42%. Abstract: The proposed research presents significant progress in the photovoltaic performance of quasi-solid state dye-sensitized solar cells (DSSCs) by synthesizing a highly electro-catalytic active activated charcoal decorated functionalized multi-walled carbon nanotube (MWCNT) composite electro-catalyst as a counter electrode (CE). The proposed carbon composite structure was synthesize by facile acid functionalization of MWCNTs followed by the addition of mesoporous activated charcoal, decorating the tubular graphitic structure of the CNTs. The carbon composite paste deposited on FTO glass by a sequential process of doctor blade coating under an air-drying technique. The porous functionalized mesoporous carbon (f-MC) with a dominant oxygen rich surface displays greatly enhanced electro-catalytic activity, low charge transfer resistance (RCT ), and exceptional cyclic stability as compared with pristine CNTs. The DSSC fabricated with f-MC CE demonstrated efficient electrochemical characteristics and photovoltaic performance when fabricated with a high-viscosity quasi-solid electrolyte. The highly conductive and porous carbon structure locates manifold sites for tri-iodide reduction reaction. High mobility of the quasi-solid electrolyte within defect rich (f-MC) surface confirmed a low RCT of (0.60 Ω.cm 2 ), and exhibited superior electrocatalytic activity compared to a conventional platinum (Pt) reference CE. The f-MC CE based DSSCs showed high power conversion efficiency (PCE) of 8.42%, exceeding the Pt reference CE of 8.11%. Based on the facile synthesis of f-MC composites and fabrication of CE, the proposed DSSCs stand out as efficient next generation solar cells.